Spectrum of autoantibody response to tumour associated antigens in normal population - Mathew, John (2013)
Early detection and diagnosis of cancer has a significant impact on cancer specific mortality as shown in randomised screening trials for breast, colon and lung cancer. However, current screening tests have limitations as they reduce cancer specific mortality for breast, colon and lung cancer by only 24%, 16% and 20% respectively, and partly as a result cancer continues to be one of the common causes of death in the developed world(Aberle et al, 2011; Hardcastle et al, 1996; Larsson et al, 1996). One of the other problems associated with current screening tests is patient compliance (mammography, colonoscopy and CT) (Jonnalagadda et al, 2012; Maurer, 1995; Pooler et al, 2012).